MEMBANGUN DNS SERVER LOKAL UNTUK MENUNJANG KEGIATAN CBT PADA SMKN 1 NEGERIKATON KABUPATEN PESAWARAN - David Listiawan; Emir Fajar Saputra; Suyitno Adi Purnomo (LPPM ITBA Dian Cipta Cendikia, 2025)
Computer Based Test (CBT) requires robust, stable, and user-friendly network infrastructure. At SMKN 1 Negerikaton, students still access CBT using numeric IP addresses, complicating use and risking errors during simultaneous tests. Furthermore, the school uses four identical servers, resulting in excessive electricity consumption, management complexity, and inefficient hardware use. This study aims to develop a local DNS Server on Debian 12 to allow students to access CBT using a human-readable domain name, improving user experience while optimizing infrastructure. The research employs the Network Development Life Cycle (NDLC), including analysis, design, simulation with VirtualBox and GNS3, implementation of BIND9 on Debian, and monitoring and management. Results show DNS resolution times improve from 200–400 ms to <50 ms. Server infrastructure was consolidated from four machines into one physical server running multiple virtual machines for DNS and CBT services. Mikrotik routers manage DHCP and NAT, and switches were upgraded to Gigabit Ethernet to handle 140 simultaneous clients effectively. This approach is low-cost, open-source, and highly effective in supporting large-scale CBT in schools. The research demonstrates a practical and replicable method for other schools seeking to modernize CBT delivery with limited budgets.